2018
DOI: 10.1002/mp.12998
|View full text |Cite
|
Sign up to set email alerts
|

A Novel method to generate on‐board 4D MRI using prior 4D MRI and on‐board kV projections from a conventional LINAC for target localization in liver SBRT

Abstract: Purpose: On-board MRI can provide superb soft tissue contrast for improving liver SBRT localization. However, the availability of on-board MRI in clinics is extremely limited. On the contrary, on-board kV imaging systems are widely available on radiotherapy machines, but its capability to localize tumors in soft tissue is limited due to its poor soft tissue contrast. This study aims to explore the feasibility of using an on-board kV imaging system and patient prior knowledge to generate on-board four-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In fact, motion models have proven to be a popular tactic in deriving 3D data from cine 2D MRI 72,73 . Harris et al 141 also developed a more accessible technique using deformable image registration with prior 4D‐MRI images to generate on‐board 4D‐MRI on linacs with on‐board kV imaging systems, as MR‐linacs are currently sparse amongst clinics, but the benefits of motion management and target verification with 4D‐MRI are substantial for radiotherapy. A different approach to obtaining 3D target verification while exploiting 2D cine MRI speeds is via super resolution, which combines two sets of complementary images (i.e., high spatial resolution with high temporal resolution) to synthesize one fully enhanced image dataset 142 .…”
Section: New and Improved 4d Imaging Solutionsmentioning
confidence: 99%
“…In fact, motion models have proven to be a popular tactic in deriving 3D data from cine 2D MRI 72,73 . Harris et al 141 also developed a more accessible technique using deformable image registration with prior 4D‐MRI images to generate on‐board 4D‐MRI on linacs with on‐board kV imaging systems, as MR‐linacs are currently sparse amongst clinics, but the benefits of motion management and target verification with 4D‐MRI are substantial for radiotherapy. A different approach to obtaining 3D target verification while exploiting 2D cine MRI speeds is via super resolution, which combines two sets of complementary images (i.e., high spatial resolution with high temporal resolution) to synthesize one fully enhanced image dataset 142 .…”
Section: New and Improved 4d Imaging Solutionsmentioning
confidence: 99%
“…The radioactive sources were simulated for the SPECT imaging unit. The detector material chosen was Cd 0.9 Zn 0.1 Te with a mass density of 5.68 g/cm 3 in the material database. The relevant low energy electromagnetic processes, such as the photoelectric effect, Bremsstrahlung, electron ionization, Compton-, Rayleigh-, and multiple electron scattering were included in the simulation to simulate xray and gamma photon interaction with aperture, object, collimator and detector materials.…”
Section: A Computing Platformsmentioning
confidence: 99%
“…Among the state-of-the-art on-treatment volumetric imaging strategies, on-board kV cone-beam CT (CBCT) using a flat-panel detector (FPD) remains the most prevalent and practical technology for IGRT due to its cost-effectiveness and/or dose efficiency as compared to on-board MRI and onboard megavoltage (MV) CBCT. [3][4][5] Based on daily pretreatment CBCT imaging, online (i.e., with a patient in the treatment position) ART is performed to improve daily dose delivery accuracy through tracking the interfraction anatomical changes of tumors during the course of RT. 6,7 However, due to the limited detection sensitivity to functional/molecular events within tumor cells that influence the radiosensitivity of tumor cells to radiation dose, conventional CBCT used in ART does not fully account for interfraction changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of rapid 2D acquisition, this method could generate volumetric images in cine fashion up to 20 frames/s [57]. Harris et al also reported that such rapid 2D acquisition can be done by planar KV fluoro images which are widely available on modern radiation linear accelerators 4D-MRI in Radiotherapy DOI: http://dx.doi.org /10.5772/intechopen.84592 (LINAC) [58,59]. This point attracts the attention since MR-based radiotherapy treatment guidance can be realized on current radiotherapy platform.…”
Section: Emerging Topics In 4d-mri Researchmentioning
confidence: 99%